Differential equations/Laplace transforms

 Educational level: this is a tertiary (university) resource.
 Type classification: this is a lesson resource.
 Subject classification: this is a mathematics resource.
 Completion status: this resource is ~25% complete.

Definition

For some problems, the Laplace transform can convert the problem into a more solvable form. The Laplace transform equation is defined as ${\displaystyle L(f(t))=\int _{0}^{\infty }e^{-st}f(t)dt=F(s)}$, for the values of ${\displaystyle s}$ such that the integral exists. There are many properties of the Laplace transform that make it desirable to work with, such as linearity, or in other words, ${\displaystyle L(\alpha f(t)+\beta g(t))=\alpha L(f(t))+\beta L(g(t))}$ .

Solution

To illustrate how to solve a differential equation using the Laplace transform, let's take the following equation: ${\displaystyle y''+2y'+y=0,y(0)=1,y'(0)=1}$ . The Laplace transform usually is suited for equations with initial conditions.

1. Take the Laplace transform of both sides (${\displaystyle L(y''+2y'+y)=L(0)=0}$ ).
2. Use the associative property to split the left side into terms (${\displaystyle L(y'')+2L(y')+L(y)=0}$ ).
3. Use the theorem ${\displaystyle L(y')=sL(y)-y(0)}$ , and by extension, ${\displaystyle L(y'')=s^{2}L(y)-sy(0)-y'(0)}$ to modify the terms into scalars and multiples of ${\displaystyle L(y)}$ (${\displaystyle s^{2}L(y)-sy(0)-y'(0)+2\left[sL(y)-y(0)\right]+L(y)=0}$ ).

4. Solve for the Laplacian (${\displaystyle L(y)={\frac {s+3}{s^{2}+2s+1}}={\frac {s+3}{(s+1)^{2}}}}$ ).
5. Take the inverse Laplace transform of both sides to get the solution, solving by method of partial fractions as needed:
(${\displaystyle L(y)={\frac {s+1+2}{(s+1)^{2}}}={\frac {1}{s+1}}+{\frac {2}{(s+1)^{2}}},y(t)=e^{-t}+2te^{-t}}$ ).
6. For reference, here are some basic Laplace transforms:
1. ${\displaystyle L(1)={\frac {1}{s}}}$
2. ${\displaystyle L(t^{n})={\frac {n!}{s^{n+1}}},n=1,2,3,\cdots }$
3. ${\displaystyle L(e^{at})={\frac {1}{s-a}}}$
4. ${\displaystyle L(\sin at)={\frac {a}{s^{2}+a^{2}}}}$
5. ${\displaystyle L(\sinh at)={\frac {a}{s^{2}-a^{2}}}}$
6. ${\displaystyle L(\cos at)={\frac {s}{s^{2}+a^{2}}}}$
7. ${\displaystyle L(\cosh at)={\frac {s}{s^{2}-a^{2}}}}$
7. For reference, here are some theorems for the Laplace transforms:
1. ${\displaystyle L(e^{at}f(t))=F(s-a)}$
2. ${\displaystyle L(t\cdot f(t))=-F'(s)}$
3. ${\displaystyle L(f^{(n)}(t))=s^{n}F(s)-s^{n-1}f(0)-s^{n-2}f(0)\cdots }$
4. ${\displaystyle L(f(t-a)\cdot U(t-a)=e^{-as}F(s),a>0}$